The T-box-encoding Dorsocross genes function in amnioserosa development and the patterning of the dorsolateral germ band downstream of Dpp - Reim, Ingolf; Lee, Hsiu-Hsiang; Frasch, Manfred (Development, 2003)
Dpp signals are responsible for establishing a variety of cell identities in dorsal and lateral areas of the early Drosophila embryo, including the extra-embryonic amnioserosa as well as different ectodermal and mesodermal cell types. Although we have a reasonably clear picture of how Dpp signaling activity is modulated spatially and temporally during these processes, a better understanding of how these signals are executed requires the identification and characterization of a collection of downstream genes that uniquely respond to these signals. In the present study, we describe three novel genes, Dorsocross1, Dorsocross2 and Dorsocross3, which are expressed downstream of Dpp in the presumptive and definitive amnioserosa, dorsal ectoderm and dorsal mesoderm. We show that these genes are good candidates for being direct targets of the Dpp signaling cascade. Dorsocross expression in the dorsal ectoderm and mesoderm is metameric and requires a combination of Dpp and Wingless signals. In addition, a transverse stripe of expression in dorsoanterior areas of early embryos is independent of Dpp. The Dorsocross genes encode closely related proteins of the T-box domain family of transcription factors. All three genes are arranged in a gene cluster, are expressed in identical patterns in embryos, and appear to be genetically redundant. By generating mutants with a loss of all three Dorsocross genes, we demonstrate that Dorsocross gene activity is crucial for the completion of differentiation, cell proliferation arrest, and survival of amnioserosa cells. In addition, we show that the Dorsocross genes are required for normal patterning of the dorsolateral ectoderm and, in particular, the repression of wingless and the ladybird homeobox genes within this area of the germ band. These findings extend our knowledge of the regulatory pathways during amnioserosa development and the patterning of the dorsolateral embryonic germ band in response to Dpp signals.
Keywords: T-box; amnioserosa; dorsal ectoderm; dpp; Wingless; Drosophila